Near-single-cycle pulses generated through post-compression on FAB1 laser at ATTOLAB-Orme facility - Hergott Jean-François (EDP Sciences, 2021)
Generating high-energy few-cycle pulses is key in the study of light-matter interaction in the regime of high field physics. Attosecond science possess the necessary time resolution to study the underlying fundamental processes but requires repetitions rates on the order the kilohertz and stabilization of the Carrier-Envelope Phase. We present here a post-compression stage delivering 3.8fs pulses with 2.5mJ coupled to a Ti: Sa based 1 kHz TW-class laser which can deliver 17.8fs pulses with 350mrad shot to shot CEP noise. This is the first step towards high-energy few-cycle post-compression of the FAB laser at ATTOLAB-Orme.